Evanescent gain for slow and stopped light in negative refractive index heterostructures - Kirby, E.I.; Hamm, J.M.; Pickering, T.W.; K. L. Tsakmakidis; Hess, O. (Physical Review B - Condensed Matter and Materials Physics, 2011)
We theoretically and numerically analyze a five-layer "trapped rainbow" waveguide made of a passive negative refractive index (NRI) core layer and gain strips in the cladding. Analytic transfer-matrix calculations and full-wave time-domain simulations are deployed to calculate, both in the frequency and in the time domain, the losses or gain experienced by complex-wave-vector and complex-frequency modes. We find excellent agreement between five distinct sets of results, showing that the use of evanescent pumping (gain) can compensate the losses in the NRI slow- and stopped-light regimes. © 2011 American Physical Society.
cited By 19